Perbandingan Pendapatan antara Usahatani Kopi dan Usahatani Jeruk di Desa Serai Kecamatan Kintamani Kabupaten Bangli - I PUTU AJUS HERYANA; I MADE SUDARMA; I GEDE SETIAWAN ADI PUTRA (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2016)
Abstract Revenue Comparisons between Coffee Farming and Orange Farming in of Serai Village Kintamani District Bangli . For the last few years the District of KintamaniBangli Regency has undergone an increase in the yield of orange, as well as the number of farmers who switched from growing coffee plants toorange plants. Because farmers assume thatcultivating orange trees is felt to be more profitable than the cultivation of Arabica coffee plants and can increase their income. The area is good for orange and coffee farming activities because it is appropriate to the climate and soil conditions for the plants, so farming is widely practiced in the area and it becomes one of the major farmingactivities done in every household. This study aimed to determine the factors that encourage the switch of coffee farming toorangefarming and compare the income of farmers from orange plants with coffee plants. Results of this study showed that, with an area of 31.3 ha,the average revenue of coffee plants was Rp232,750,000.00 and orange trees showed the average value of Rp. 263,200,000.00. Keywords : Farming, yield, income